2006
DOI: 10.1177/1077801206292672
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Sexual Assault of Women With Disabilities

Abstract: North Carolina women were surveyed to examine whether women's disability status was associated with their risk of being assaulted within the past year. Women's violence experiences were classified into three groups: no violence, physical assault only (without sexual assault), and sexual assault (with or without physical assault). Multivariable analysis revealed that women with disabilities were not significantly more likely than women without disabilities to have experienced physical assault alone within the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
133
3
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(153 citation statements)
references
References 20 publications
7
133
3
8
Order By: Relevance
“…Women with disabilities are likely to be easier to experience sexual violence compare to other women since the perpetrator thinks that disabled women are relatively powerless to refuse. Furthermore, sexual violence on disabled is probably easier to be manipulated so that violence may occur, the perpetrator also thinks that women with disabilities will not report the attack they undergo (Martin et al, 2006). Devries et al, (2014) states that disabled children are 3 until 4 times more at risk for experiencing violence including sexual violence compare to non-disabled children.…”
Section: Discussionmentioning
confidence: 99%
“…Women with disabilities are likely to be easier to experience sexual violence compare to other women since the perpetrator thinks that disabled women are relatively powerless to refuse. Furthermore, sexual violence on disabled is probably easier to be manipulated so that violence may occur, the perpetrator also thinks that women with disabilities will not report the attack they undergo (Martin et al, 2006). Devries et al, (2014) states that disabled children are 3 until 4 times more at risk for experiencing violence including sexual violence compare to non-disabled children.…”
Section: Discussionmentioning
confidence: 99%
“…When a woman with a disability seeks IPV related assistance, the goal may not always be to leave the abusive relationship, understanding that some women will be reluctant if the perpetrator is someone on whom she depends for assistance with daily needs (Martin et al, 2006). Women with disabilities also face the loss of accessible housing, barriers in the criminal justice system, and threats to their independence if they report abuse, among a host of concerns (Ortoleva & Lewis, 2012).…”
Section: The Survivor's Need To Be Respected Informed Connected Anmentioning
confidence: 99%
“…Feminist disability theory integrates feminism with its emphasis on the inequalities inherent in the male dominated, patriarchal society and disability theory with the focus on the effects of marginalization and unequal treatment for women who have a disability and suffer from abuse (Barranti & Yuen, 2008;Fiduccia & Wolfe, 1999;Garland-Thomson, 2001;Mays, 2006;Rousso, 2001). Recent studies conducted in the U.S. have found that compared to women without disabilities, women with disabilities are more likely to experience intimate partner violence (Brownridge, 2006;Martin et al, 2006) and longer durations of abuse (Nosek, Howland, & Hughes, 2001). Merely applying traditional theories that focus on male domination and patriarchy to the experiences of abuse suffered by women who also have disabilities has prevented an effective means of addressing these unique problems (Center for Research on Women with Disabilities, 2002;Frantz, Carey, & Bryen, 2006;Jones, 2007;Mays, 2006).…”
Section: Feminist Disability Theorymentioning
confidence: 99%
“…Several studies found that partners of women with disabilities were more likely to be perpetrators of IPV than partners of women without disabilities (Collins et al, 1999;Martin et al, 2006;McFarlane et al, 2001;Young et al, 1997).…”
Section: Disability Theorymentioning
confidence: 99%